Structural Bionic Design for Digging Shovel of Cassava Harvester Considering Soil Mechanics - Shihao Liu; Shaojie Weng; Yulan Liao; Dongyun Zhu (Applied Bionics and Biomechanics)
In order to improve the working performance of cassava harvester, structural bionic design for its digging shovel was conducted. Taking the oriental mole cricket's paws as bionic prototype, a new structural bionic design method for digging shovel was established, which considers the morphology-configuration-function coupling bionic. A comprehensive performance comparison method was proposed, which is used to select the bionic design schemes. The proposed bionic design method was used to improve digging shovel structure of a digging-pulling style cassava harvester, and nine bionic-type digging shovels were obtained with considering the impact of soil mechanics. After conducting mechanical properties comparative analysis for bionic-type digging shovels, the bionic design rules were summed up, and the optimal design scheme of digging shovel was obtained through combining the proposed comprehensive performance comparison method with Analytic Hierarchy Process (AHP). Studies have shown that bionic design method not only can improve the overall mechanical properties of digging shovel, but also can help to improve the harvesting effect of cassava harvester, which provides a new idea for crops harvesting machinery's structural optimization design.